Applying Earth Observation Data for Urban Land-Use Change Mapping (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The Special Issue “Applying Earth Observation Data for Urban Land-Use Change Mapping” focuses on the science of Earth observation data, aiming to process, analyze, and monitor the development and impact of urbanized areas from social, economic, environmental, and other land-related perspectives. This Special Issue particularly favors the use of artificial intelligence and machine learning algorithms for processing spatial big data and correlating it with in situ measurements. The articles in this Special Issue present theoretical and practical approaches to urban processes and are a collection of applied and review articles. Interdisciplinary manuscripts are also particularly welcome.